Suicide Attempt in Patients With Gambling Disorder—Associations With Comorbidity Including Substance Use Disorders - Håkansson, Anders; Karlsson, Anna (Frontiers in Psychiatry, 2020)
Background: Gambling disorder is known to be associated with increased risk of suicidal behavior. However, relatively little is known about how the risk of suicide attempts in gambling disorder is influenced by comorbid alcohol or drug use disorders, as well as other psychiatric conditions. Methods: The present study is a nationwide, diagnostic register study assessing the risk of suicide attempts (including fatal ones) in gambling disorder in Sweden in 2005-2016. Results: In a total of 2,099 individuals (23 percent women) with gambling disorder, 417 individuals had a suicide attempt (including 10 fatal cases of suicide) during the study period. Suicidal behavior was more common in patients with substance use disorders at any time during the study period (50 percent if both alcohol and drug use disorders were present, and 10 percent if none of these were present). In logistic regression, suicidal behavior was significantly associated with female gender (OR 2.13 [1.63-2.78]), mood disorders (OR 2.65 [2.00-3.50]), anxiety disorders (OR 1.78 [1.34-2.35]), and with alcohol (OR 1.95 [1.51-2.51]) or drug use disorders (OR 3.60 [2.76-4.69]), respectively. Conclusions: Suicidal behavior in clinical gambling disorder patients is common, but markedly more common in the presence of substance use and other comorbid disorders.